Implementasi Kebijakan Peraturan Kepala Badan Pengawasan Keuangan dan Pembangunan Republik Indonesia Nomor 6 Tahun 2015 - Hakim, Muhammad; Kusmanto, Heri; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The purpose of this research is to find out and analyze the Implementation of the factors that become obstacles in the implementation of Perka BPKP RI No. 6 of 2015 in the Inspectorate of Aceh Tamiang Regency. The form of this research is descriptive qualitative, the data used in this study are primary data and secondary data. Primary data that are generally used in qualitative research include: Interviews, Observation and Documentation. While secondary data is data obtained from literature and documents. Based on the description of the results of research and discussion, conclusions are drawn regarding the Implementation of Perka BPKP RI No. 6 of 2015 Concerning the Grand Design of APIP Capability Improvement in the Inspectorate of Aceh Tamiang Regency based on Edward III's theory, it has been going well but not yet maximally implemented.